The Effect of Paternal Age on Relapse in First-Episode Schizophrenia. (August 2015) - Hui, Christy L M; Chiu, Cindy P Y; Li, Yuet-Keung; Law, Chi-Wing; Chang, Wing-Chung; Chan, Sherry K W; Lee, Edwin H M; Sham, Pak; Chen, Eric Y H
Objective: Multiple etiological and prognostic factors have been implied in schizophrenia and its outcome. Advanced paternal age has been reported as a risk factor in schizophrenia. Whether this may affect schizophrenia outcome was not previously studied. We hypothesized that advanced paternal age may have a negative effect on the outcome of relapse in schizophrenia. Method: We interviewed 191 patients with first-episode schizophrenia and their relatives for parental ages, sociodemographic factors at birth, birth rank, family history of psychotic disorders, and obstetric complications. The outcome measure was the presence of relapse at the end of the first year of treatment. Results: In the 1-year follow-up period, 42 (22%) patients experienced 1 or more relapses. The mean paternal age was 34.62 years (SD 7.69). Patients who relapsed had significantly higher paternal age, poorer medication adherence, were female, and were hospitalized at onset, compared with patients who did not relapse. A multivariate regression analysis showed that advanced paternal age (OR 1.05, 95% CI 1.01 to 1.10), medication nonadherence (OR 2.37, 95% CI 1.12 to 4.99), and female sex (OR 2.44, 95% CI 1.14 to 5.24) independently contributed to a higher risk of relapse. Analysis between different paternal age groups found a significantly higher relapse rate with paternal age over 40. Conclusions: Advanced paternal age is found to be modestly but significantly related to more relapses, and such an effect is the strongest at a cut-off of paternal age of 40 years or older. The effect is less likely to be mediated through less effective parental supervision or nonadherence to medication. Other possible biological mechanisms need further explorations.